IMPLIKASIINFORMATIONASYMMETRYTERHADAPTINGKAT PENGEMBALIAN SAHAM (STUDI PADAPERUSAHAAN YANGTERDAFTARDI INDEKSSRI- KEHATI PERIODE 2015-2017) - MAY AUDINA SIHOMBING (SOSIALITA, 2019)
Condition in which the differencebetween the informationthat indicatedinvestorsmay affect the amountofprofit fromthe investmentmadebythe investor.Basedonthese conditions,thisstudywasconductedtodetermine the effectofinformationasymmetryon stockreturnsreceivedby investors.Thisstudyusesthecontrolvariablesoffirmsize (SIZE),Return onAssets(ROA),andEarningperShare(EPS).Thesamplesinthis study using purposivesampling andobtainedasampleof10companiesthatwasregisteredin SRI-KEHATIindex. Data analysistechniqueused ismultiple linearregression approach usingpaneldata andusingprogramanalysis toolseviews 7. Basedont-testresultsshowedthat thevariableinformationasymmetryispartially significanteffectonstockreturnsandfirmsizevariable(SIZE),ReturnonAssets (ROA), and Earning perShare(EPS)partially no significanteffecton stock returns. Based on the resultsof the F-testshowsthat there issimultaneouslya significant influencebetween the variablesof information asymmetry, firmsize(SIZE),ReturnonAssets(ROA),and Earning perShare (EPS)ofthe stock returns. Condition in which the differencebetween the informationthat indicatedinvestorsmay affect the amountofprofit fromthe investmentmadebythe investor.Basedonthese conditions,thisstudywasconductedtodetermine the effectofinformationasymmetryon stockreturnsreceivedby investors.Thisstudyusesthecontrolvariablesoffirmsize (SIZE),Return onAssets(ROA),andEarningperShare(EPS).Thesamplesinthis study using purposivesampling andobtainedasampleof10companiesthatwasregisteredin SRI-KEHATIindex. Data analysistechniqueused ismultiple linearregression approach usingpaneldata andusingprogramanalysis toolseviews 7. Basedont-testresultsshowedthat thevariableinformationasymmetryispartially significanteffectonstockreturnsandfirmsizevariable(SIZE),ReturnonAssets (ROA), and Earning perShare(EPS)partially no significanteffecton stock returns. Based on the resultsof the F-testshowsthat there issimultaneouslya significant influencebetween the variablesof information asymmetry, firmsize(SIZE),ReturnonAssets(ROA),and Earning perShare (EPS)ofthe stock returns.